The large scale calculations of the negative-parity states stricture in 24mg nucleus - Anwer A.M, Al-Sammarrea; Firas, A. Ahmed; Abdurahim, Okhunov (Naukova Dumka, 2021)
The negative – parity states of 24Mg nucleus are studied based on the calculations of energy levels, total squared form factors, and transition probability using the large model space PSDPF Hamiltonian. Comparison between the experimental and theoretical states showed a good agreement under specific restrictions. The theoretical calculation of negative – parity states presented high sensitivity to the restriction applied to the nucleons’ configuration. The total squared form factors and transition probabilities are calculated and compared with the available experimental data. It has been found that one – body density – matrix elements obtained from the PSDPF Hamiltonian and the wave functions of radial single particle matrix elements which are calculated with harmonic-oscillator potential are in good agreement with experimental data by changing the center of mass correction values.